KNOWLEDGE AND PRACTICE OF THE GLUTEN-FREE DIET BY NON-CELIAC PEOPLE (REMUNOM, 2025)
Introduction: the practice of a gluten-free diet is growing, motivated by a belief that this attitude leads to a healthier diet, including weight loss. Objective: to fill the information gap regarding the knowledge and practice of a gluten-free diet by non-celiac people. Method: the sample consisted of 42 participants who responded to an online questionnaire between January and June 2019. Results: the majority of respondents are women between 31 and 40 years old with schooling ranging from college to graduate. Of these (N = 26), live in the southeastern region of the national territory. Among the sources of information about the gluten-free diet, “nutritionists and doctors” stand out with 73.8% (N = 31), followed by social media and internet videos with 38% (N = 16); magazines and newspapers with 26.1% (N = 11) and friends and family with 11.9% (N = 5). Conclusion: in the population evaluated, the adoption of a gluten-free diet by non-celiac people is largely influenced by nutritionists and doctors, in addition to being carried out without the need and adequate knowledge, resulting in situations that are harmful to health.